2017
DOI: 10.13189/ujer.2017.050118
|View full text |Cite
|
Sign up to set email alerts
|

What Makes a Good Teacher?

Abstract: The introduction of the new Teacher CareerModel, the School Inspectorate and the Complex School Assessment imply the basic question "What makes a good teacher?" The scholars have been focusing on the issue for a long period of time. The target of the recent studies is the teachers', school principals' and the teacher students' beliefs. The primary and secondary school students' beliefs have been neglected. This study presents the results of a research in which we explore the secondary school students' expectat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…The teachers must effectively communicate and interact with students, reward students equally for their behaviours, challenge students to achieve high scores, make classes enjoyable, and show passion in teaching students (Gao & Liu, 2013). Ida (2017) observed that the traits of an effective teacher were linked to their personality traits, teacher's abilities and skills, and professional competencies. An effective teacher is one who is fair, friendly, patient, confident, joyful, objective, and knowledgeable (Ida, 2017).…”
Section: Trainee Teachers' Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…The teachers must effectively communicate and interact with students, reward students equally for their behaviours, challenge students to achieve high scores, make classes enjoyable, and show passion in teaching students (Gao & Liu, 2013). Ida (2017) observed that the traits of an effective teacher were linked to their personality traits, teacher's abilities and skills, and professional competencies. An effective teacher is one who is fair, friendly, patient, confident, joyful, objective, and knowledgeable (Ida, 2017).…”
Section: Trainee Teachers' Skillsmentioning
confidence: 99%
“…Ida (2017) observed that the traits of an effective teacher were linked to their personality traits, teacher's abilities and skills, and professional competencies. An effective teacher is one who is fair, friendly, patient, confident, joyful, objective, and knowledgeable (Ida, 2017).…”
Section: Trainee Teachers' Skillsmentioning
confidence: 99%
“…Regarding to the quality of teachers, Coe et al (2014) claimed that the features to make effective teachers include: deep content knowledge and knowledge of materials/ method to be taught to students, high quality in giving instruction which is specific and practical, create supportive classroom climate and positive interaction, rich classroom management skills, having professional behaviors to develop professional practice, supporting colleagues, and communicating with parents. In light of this discussion, Ida (2017) pointed out that among the required qualities of (a) teachers" content knowledge, (b) planning pedagogical processes and activities, (c) develop students" personality, (d) develop students" sense of community, (e) continuously analyze and assess pedagogical processes, (f) professional communication and cooperation, (g) professional commitment and responsibility, the factors of supporting students" learning is the most significant competence of an effective and quality teacher.…”
Section: Introductionmentioning
confidence: 86%
“…The needed quality of teachers consists of teacher qualifications, teacher characteristics, teacher instruction (practices), and teacher effectiveness (Goe & Stickler, 2008). Ida (2017) concluded that personal traits and professional competencies are required qualities of effective teachers. The required quality of teacher is diverse and it must be trained during teacher preparation process (Ko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These activities are often challenging because the teachers' role is not so simple. Szucs (2017) reported that students have very high expectations for their teachers. Her research found out that students would like teachers who are willing to acquire more learning in the subject.…”
Section: Challenges and Problems In Teaching Social Studiesmentioning
confidence: 99%